YY‐11, a camel milk‐derived peptide, inhibits TGF‐β‐mediated atherogenic signaling in human vascular smooth muscle cells. Issue 3 (27th July 2021) - Hussain, Humaira; Cao, Yingnan; Mohamad, Raafat; Afroz, Rizwana; Zhou, Ying; Moyle, Peter; Bansal, Nidhi; Wattoo, Feroza Hamid; Kamato, Danielle; Little, Peter J.
Abstract: Atherosclerosis, the major underlying pathology of cardiovascular disease, commences with the binding and trapping of lipids on modified proteoglycans, with hyperelongated glycosaminoglycan chains. Transforming growth factor (TGF)‐β stimulates glycosaminoglycan elongation in vascular smooth muscle cells. We have recently shown that this TGF‐β signaling pathway involves reactive oxygen species (ROS). YY‐11 is a dodecapeptide derived from camel milk and it has antioxidant activity. We have investigated the role of YY‐11 in blocking ROS signaling and downstream atherogenic responses. YY‐11 inhibited TGF‐β stimulated ROS production and inhibited the expression of genes for glycosaminoglycan chain elongation as a component of an in vitro model of atherosclerosis. This study provides a biochemical mechanism for the role of camel milk as a potential nutritional product to contribute to the worldwide amelioration of cardiovascular disease. Practical applications: The identification of readily accessible foods with antioxidant properties would provide a convenient and cost‐effective approach community wide reducing oxidative stress induced pathologies such as atherosclerosis. We demonstrate that camel milk‐derived peptide is an antioxidant that can inhibit growth factor‐mediated proteoglycan modification in vitro. As proteoglycan modification is being recognized as one of the earliest atherogenic responses, these data support the notion of camel milk as a suitable nutritional product to contribute to the prevention of early stage of atherosclerosis development. Abstract : Camel milk‐derived peptide YY‐11 inhibits TGF‐β stimulated ROS and downstream transcription factors Smad2 phosphorylation in the linker region. Atherosclerosis commences with the binding of lipids to elongated glycosaminoglycan chains on proteoglycans. TGF‐β stimulated the expression of genes associated with glycosaminoglycan chain elongation. YY‐11 inhibits TGF‐β stimulated expression of elongation genes and as such supports the notion that camel milk may be a suitable nutritional product to prevent atherosclerosis.